Hydrogel Platforms: A Hydrogel Platform that Incorporates Laminin Isoforms for Efficient Presentation of Growth Factors – Neural Growth and Osteogenesis (Adv. Funct. Mater. 21/2021). (24th May 2021) - Dobre, Oana; Oliva, Mariana A. G.; Ciccone, Giuseppe; Trujillo, Sara; Rodrigo‐Navarro, Aleixandre; Venters, Douglas Cormac; Llopis‐Hernandez, Virginia; Vassalli, Massimo; Gonzalez‐Garcia, Cristina; Dalby, Matthew J.; Salmeron‐Sanchez, Manuel
Abstract : In article number 2010225, Manuel Salmeron‐Sanchez and co‐workers develop hydrogels that incorporate specific laminin isoforms. Laminins are ECM molecules that are tissue specific, promote integrin binding, and sequester growth factors. The versatility of the system to engineer in vitro 3D cultures of controlled stiffness that promote mesenchymal stem cell differentiation (using LM 521) or promote neural growth (using LM 411) is demonstrated.